The Role of Oocyte Quality in Explaining “Unexplained” Infertility - Homer, Hayden Anthony (Seminars in Reproductive Medicine, 2020)
Infertility is described as unexplained when pregnancy does not occur despite ovulation, patent Fallopian tubes, and normal semen parameters. Oocyte developmental competence (or quality) is rate-limiting for pregnancy success as oocytes provide virtually all the cellular building blocks including mitochondria required during embryogenesis. However, available tests estimate oocyte numbers (anti-Müllerian hormone, follicle-stimulating hormone and antral follicle count) and ovulation (luteal phase serum progesterone) but not the third, and most pivotal, oocyte-specific parameter, quality. Severe depletion of the follicular reserve manifests as premature ovarian insufficiency and is an obvious cause of anovulation with overt symptoms and clear diagnostic criteria. In contrast, there are no biomarkers of poor oocyte quality other than through in vitro fertilization when readouts of oocyte quality such as preimplantation embryo development can be assessed. The most common cause of poor oocyte quality is natural aging, which is strongly tied to reduced oocyte mitochondrial efficiency and increased oxidative stress. In younger women, quality may also be impaired due to accelerated aging or sporadic genetic mutations which cause severe defects during oocyte and embryo development. Thus, poor oocyte quality often provides an explanation for infertility, but because it cannot be measured using conventional tests, many cases of infertility are often incorrectly labeled “unexplained.” Since female age remains the best predictor of oocyte quality, age over 37 years should be considered an independent diagnostic criterion.
Keywords: oocytes; oocyte quality; unexplained infertility; oocyte aging